Gambaran Kesehatan Mental Istri Penderita Stroke dalam Upaya Peningkatan Kualitas Hidup (The Wife’s Mental Health Overview of the Stroke Patient in Order to Incease the Patient’s Quality of Life) - Vini Rahmi Alviani; Husni Abdul Gani; Elfian Zulkarnain (Pustaka Kesehatan, 2017)
Stroke occurred in the productive age group that became the backbone of the family. Family emotional support especially the wife to her husband who suffered a stroke was one support provided. The purpose of thwas study was to describe the picture of economic conditions, knowledge, attitudes, practices and mental health in asswasting wife's husband suffered a stroke. Thwas research was a qualitative descriptive study. Determination of informants in thwas study using purposive technique. Mechanical collection through interviews, observation of non-participatory and triangulation methods. The study says that changes in the economic conditions experienced by a barrier that most felt, the earned income can not meet their daily needs. Knowledge possessed by surrounding the patient's wife to accompany her husband during the experience. Wife feel the pressure of life, because in addition to the need to take cwere of husbands who have limited motor, informants also must replace a husband who should be the head of the family. Wife direct role in meeting the daily needs of the husband. Wife able to adapt to the conditions experienced. Thus, it can be seen that the wife has a good adjustment to the reality faced. Keywords: Mental health, the wife of a patient, stroke